Incidence of endoleak type IA in patients undergoing chimney endovascular aortic repair (ChEVAR) vs. standard endovascular repair - Rabellino, Martin (2024)
Background. Almost half of endovascular aortic aneurysm repair (EVAR) procedures are performed in hostile anatomy, increasing the risk of procedure related complications such as type IA endoleaks, which may be prevented with the chimney technique in EVAR (ChEVAR). Objective: Our aim is to describe the differential characteristics between EVAR in favorable anatomy and ChEVAR in hostile necks. Materials and methods. A cohort of patients with infrarenal abdominal aortic aneurysms (AAA) that were treated with EVAR or ChEVAR were included. The primary outcome was the incidence of type IA endoleak. Secondary outcomes were the rate of chimney occlusion, reintervention, migration, rupture, acute limb ischemia, sac growth, and aneurysm- related mortality during the follow-up period. Results. With a median follow-up of 11.5 months, 79 patients were treated with EVAR and 21 with ChEVAR. The overall age was 76.49 ± 7.32 years old, and 82% were male. The ChEVAR cohort had a higher prevalence of tobacco use than the EVAR cohort (38.1% vs. 17.7%, p =0.041), and a shorter neck (7.88 mm ± 5.73 vs 36.28 mm ± 13.73, p<0.001). There were no differences in type IA endoleak incidence between the groups (a single endoleak type IA in the EVAR group, p = 0.309). One patient experienced an asymptomatic chimney occlusion in the ChEVAR group, and another patient required a reintervention due to chimney occlusion. Sac regression and reinterventions were not different between groups. There were no migration, rupture, acute limb ischemia, or aneurysm-related mortality events. Conclusions. In patients with abdominal aortic aneurysms, ChEVAR in hostile necks had similar event rates to EVAR in favorable necks.